1991
DOI: 10.1007/bf00235185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate loading and underwater exercise on circulating cortisol, insulin and urinary losses of chromium and zinc

Abstract: The effects of carbohydrate loading on relative stress responses of eight male subjects performing intermittent leg exercise at 80% maximum oxygen consumption during headout immersion in 25 degrees C water were tested. Carbohydrate loading increased the number of work cycles completed, with less physical stress compared with that completed following the control diet period. Pre-exercise serum cortisol values were similar on both diets prior to exercise but following exercise control values were greater (1152, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…These data are in accordance with the results of Anderson et al [34]. The low carbohydrate intake may affect the cortisol levels [35]. Therefore, higher concentrations of cortisol may be a main factor in the susceptibility to infections and injuries because of its immunosuppressive role [36].…”
Section: Discussionsupporting
confidence: 91%
“…These data are in accordance with the results of Anderson et al [34]. The low carbohydrate intake may affect the cortisol levels [35]. Therefore, higher concentrations of cortisol may be a main factor in the susceptibility to infections and injuries because of its immunosuppressive role [36].…”
Section: Discussionsupporting
confidence: 91%
“…Other stresses including pregnancy, lactation, exercise, infection and physical trauma also increase Cr losses and requirements ( Table I). The effects of stress on urinary Cr losses are correlated directly with the stress hormone cortisol [17].…”
Section: Chromium Requirement and Stressmentioning
confidence: 99%
“…Campbell and Anderson [18] reported that exercise significantly increased urinary chromium excretion. Similarly, it was demonstrated that underwater exercise reduced levels of chromium in serum and that carbohydrate loading inhibited this decrease [19]. It was reported that exercise did not affect cobalt levels in triathletes [20], while cadmium levels in athletes were found lower than those in controls [21].…”
Section: Discussionmentioning
confidence: 96%